ANALISIS METODE COST PLUS PRICING DAN TARGET COSTING ALAM MENENTUKAN HARGA JUAL AL-JARWAL BAKERY - Muhammad Luthfie Hasan; Tri Handayani Amaliah; Hartati Tuli (Al-Buhuts, 2026)
Competition in the bakery industry requires companies to implement pricing strategies that can maintain competitiveness while increasing profitability. This study aims to analyze and compare the conventional selling price-setting method used by Al-Jarwal Bakery with the Cost-Plus Pricing and Target Costing methods. The study employs a quantitative descriptive approach, focusing on two flagship products: Chocolate Pandan Bread and Chocolate Peanut Bread. Research data were collected through observation, interviews, and documentation of the company’s production costs, then analyzed using calculations of the cost of goods sold and pricing simulations based on each method. The results show that the conventional method used by the company yields a lower profit margin compared to the Cost Plus Pricing and Target Costing methods. The application of the Cost Plus Pricing method results in a higher selling price with a more certain profit margin, while the Target Costing method proved to be more effective because it was able to maintain a selling price of Rp1,400 in line with market prices while simultaneously increasing the profit margin through production cost efficiency. Cumulatively, the implementation of Target Costing reduces the cost of goods sold by Rp32,579,524 per year compared to the method currently used by the company. These findings indicate that Target Costing is a more effective approach for improving profitability without compromising price competitiveness and can serve as an alternative pricing strategy for businesses in the food industry.